Fatty-acid-derived ester-urethane macromonomers synthesized using bismuth and zinc catalysts. (5th May 2022) - Niedźwiedź, Malwina J.; Demirci, Gokhan; Kantor-Malujdy, Nina; Sobolewski, Peter; El Fray, Miroslawa
Graphical abstract: Highlights: Fatty acid derived ester-urethane telechelic macromonomers were synthesized with Bi and Zn catalysts. Syntheses were performed in ethyl acetate (a green solvent) Reaction kinetics of non-toxic Bi and Zn catalysts were compared to organotin catalyst. Elastomeric films were created in air and argon by photopolymerization. The use of non-toxic solvent and catalysts increased cell viability in vitro. Abstract: Photocurable materials that can be delivered as liquids and rapidly (within seconds) cured in situ using UV light are gaining increased interest in advanced minimally invasive procedures. The aim of this work was to synthesize and characterize fatty-acid-derived ester-urethane telechelic (methacrylate) macromonomers, suitable for photopolymerization. The commonly used dibutyltin dilaurate catalyst was replaced with bismuth neodecanoate, bismuth tris(2-ethylhexanoate), and zinc (II) acetyloacetonate as less-toxic alternative catalysts. Additionally, ethyl acetate was used as a "green" solvent. The progress of the two-step synthesis was monitored with infrared spectroscopy. The chemical structure and molecular weight of the obtained viscous materials was characterized with nuclear magnetic resonance spectroscopy and gel permeation chromatography. Photocrosslinking of the macromonomers into elastomeric films was achieved using 150 s per spot of UV light (20 mW/cm 2 ) exposure. Mechanical tensile testing of the films indicated their elasticity up to 120% and low modulus typical for soft and elastomeric materials. Finally, in vitro cytotoxicity tests showed high cell viability for the case of materials synthesized using bismuth and zinc catalysts. Overall, our results indicate that bismuth and zinc catalysts are excellent alternatives to organotin compounds in the synthesis of photocurable methacrylate ester-urethanes with improved environmental and safety profile, and for potential biomedical applications.